Landscape Design of Future City Community Public Space in Tianjin Post-COVID-19 - Tingting , Zhao; Phanthabutr, Saowaluck (Journal of Roi Kaensarn Academi, 2023)
The new crown epidemic in 2020 has had a profound impact on the world and changed people's way of life. In China, under the normalization of the epidemic, people's demand for shared space in communities has changed. The purpose of this research is to find out the residential landscape design solutions of Tianjin Future City under the impact of Covid-19 according to the needs of the community after the normalization of the epidemic, and to create and design the landscape design for the shared space of Tianjin Future City 3A community after the COVID-19 epidemic. Taking the 8A community of Tianjin Future City as the research population, 200 people were selected as a sample, and the needs of the target group were collected through questionnaires and interviews. The study found that the epidemic has made community residents pay more attention to personal safety and health, and have higher requirements for comprehensive activity venues, the needs of the elderly and children, natural landscapes and social needs. Through the analysis of questionnaires and interview results, it is found that the needs of residents after the epidemic are as follows: (1) Pay attention to the needs of community personal safety, health safety, property safety, and traffic safety. (2) Increase the design of a comprehensive activity venue, that is, a comprehensive activity venue that integrates rest venues, basketball courts, and game fields, hoping to increase the fun and interactivity of the venue. (3) Pay attention to the activity venues and sports needs of the elderly (old man) and children. (4) Looking forward to being close to nature and increasing the diversity of natural landscape elements and greening quantity and varieties in the residential area. (5) Hope to interact with others, social needs strengthened.